Prototipo robótico “FISIOTY” y su relación en la estimulación sensorial en niños con discapacidad que acuden a la Unidad Educativa Especializada “Ayúdanos a Empezar” Babahoyo periodo octubre 2024 – abril 2025. - Cela Acosta, Keyla Anavela (2025)
Sensory stimulation plays a fundamental role in the treatment of children with disabilities, as it directly influences their motor, cognitive and emotional development, facilitating sensory integration and neuroplasticity. In the field of pediatric physiotherapy, this stimulation is used to enhance mobility, motor coordination, postural control and general functionality of the child. The thesis project presented aims at the design and validation of a robotic prototype called “FISIOTY”, aimed at the sensory and motor stimulation of children with disabilities in the Specialized Educational Unit “Ayúdanos a Empezar” in Babahoyo. This interactive device is integrated into pediatric physiotherapy sessions, combining physical rehabilitation activities with sensory stimuli that allow the child to process and integrate information through their sensory channels. The prototype seeks to improve functional mobility and encourage the active participation of children in the therapeutic process, supporting motor rehabilitation, muscle strengthening, as well as improving coordination and balance. The evaluation of the prototype's effectiveness was carried out using direct observation techniques, a sensory evaluation scale, and interviews with parents and teachers. This project proposes a personalized and inclusive intervention, where robotic technology becomes a complementary tool in physiotherapy treatment.